Analyzing Land Surface Temperature on Green Open Space at the Brawijaya University - Wibisono, Iwan (Jurnal Pembangunan dan Alam Lestari, 2026)
The provision of Green Open Space (GOS) in Malang City has not yet fulfilled the minimum proportion mandated by Law Number 26 of 2007 on Spatial Planning. This shortfall has contributed to the emergence of the Urban Heat Island (UHI) phenomenon, which poses increasing environmental and thermal comfort challenges in urban areas. One of the primary drivers of UHI in Malang City is the extensive conversion of green land into built-up areas, particularly for residential development. As urban expansion continues, private residential land holds significant potential to function as supplementary green open space, thereby contributing to urban microclimate regulation. This study aims to analyze differences in land surface temperature across various green open space components by comparing hardscape and softscape elements within three Green Open Spaces located at Universitas Brawijaya. Land surface temperature measurements were conducted over three consecutive days, with observations carried out for 12 hours each day at two-hour intervals. The results indicate a clear distinction between surface temperatures of hardscape and softscape materials. Softscape elements consistently exhibited lower surface temperatures compared to hardscape materials, demonstrating their effectiveness in mitigating heat accumulation. Among the materials analyzed, andesite exhibited the highest surface temperature, reaching up to 37°C, while water bodies, such as ponds, recorded the lowest surface temperature at approximately 23°C. These findings highlight the critical role of softscape components, particularly vegetation and water features, in reducing surface temperatures and mitigating UHI effects. Keywords: Green Open space, Hardscape, Softscape, Surface Temperature